Two decades of research trends and transformations in manufacturing sustainability: a systematic literature review and future research agenda - Jamwal, Anbesh; Agrawal, Rajeev; Sharma, Monica; Kumar, Anil; Luthra, Sunil; Pongsakornrungsilp, Siwarit (Springer, 2021)
Sustainable manufacturing (SM) has become an emerging research topic in sustainability due to strict government policies, social awareness, and rapid information and technology changes. Industries are now adopting Industry 4.0 technologies to compete in the global market competition. Very few studies discussed the evolution of SM and the related research themes that evolved in recent years. This study aims to identify the research themes and research transformation evolved in SM in the last twenty-one years. The impact of most productive authors, journals and countries is evaluated by citation analysis, while the co-occurrence of keywords is done to identify the thematic evolution and trending topics in SM. The results of this study provide a clear and detailed picture of various research themes that evolved in SM from 1999 to 2020 i.e., sustainable planning and scheduling, sustainable supply chain, lean and environmental management, sustainable machining, decision making, Industry 4.0 and Lean production systems. The number of publications related to Sustainability and Industry 4.0 has increased in the last 3 years. Cluster analysis shows the evolution of many new trending topics in SM i.e., SM in Industry 4.0. Challenges and enabling factors for the sustainable manufacturing practices have identified and role of decision making in SM implementation is discussed. The content analysis on major research themes in SM is discussed with the help of cluster analysis. Based on the literature analysis a comprehensive research framework for future research work is proposed in Industry 4.0 context. The results obtained from this study will be valuable for academia and practitioners enabling them to be updated about the latest developments in SM research.